Post-fire changes in soil of pine stands - Voron, V. P.; Melnyk, Ye.Ye.; Ivanicheva, Ye. V.; Timochuk, I. V.; Tkach, O. M. (Forestry and Forest Melioration, 2019)
Introduction As a result of surface fires, many factors in pine stands change, namely a structure, composition and properties of both forest litter and upper layers of soil. The microclimate changes as well. Changes in the physical, chemical and biological properties of soils occur as due to high temperatures, so due to ash. At that, fires can have different impact on soil properties. It depends on physical and geographical conditions, the type of the stand and forest site type, as well as on a type and intensity of the fire. Therefore, forest fires’ nature and degree of their impact on soils in different conditions requires a thorough study. Materials and Methods Soil properties changes caused by surface fires were studied in the pine forests of several state forest enterprises in Ukrainian Polissya, Forest-Steppe and Steppe. Sample plots were laid out in similar middle-aged pure pine forests, aged between 50 and 70 in the most commonly damaged by fires forest site types (fresh and moist fairly infertile sites for Polissya and Forest-Steppe; very dry and dry infertile sites for Steppe). Soil analysis was carried out over different periods, as immediately after the fire, so during longer periods (up to one and a half years). The forest site capacity dynamics of soils in pine stands damaged by surface fires were studied by means of generally accepted methods. The content of available for plants nutrient forms, characteristics of ion-salt modes and cation-exchange properties of soils were used as diagnostic indicators. Results Combustion of the forest litter samples from all natural zones showed that the maximum value of pH response of the ash of the burnt forest litter in the studied pine stands immediately after burning was highly alkaline (8.5–8.70). The minimum value for Polissya was 7.71 (medium alkaline), for Forest-Steppe it was 8.70 (highly alkaline), for Steppe – 7.57 (slightly alkaline). The studies in sample plots established in different site types in pine stands within Polissya, Forest-Steppe and Steppe showed that the pH response of the ash of the forest litter burnt during the experiment, ranges from highly alkaline (8.69) to medium alkaline (7.71). No dependence of the forest litter ash pH value on forest site types was detected. The cation contents in soil water extraction in all studied conditions demonstrated that two weeks after the fire the ash contained potassium and calcium 10 times more than in the upper soil layer and in control. Moreover, both sodium and magnesium contents were 6–10 times higher, and hydrocarbonate contents were more than 20 times higher. Thus, in the forest-steppe conditions, in the case where the forest litter was not completely combusted, after 2 weeks, the hydrocarbonate contents increased 4.5 times; after three months, the ash contained 2–4 times more alkaline cations and hydrocarbonates. Therefore, at the time of the first analysis of the ash, alkaline elements, due to the forest litter, were not washed into the soil. Quite different trends were found in soils where the litter was completely combusted. The total content of alkaline cations increased 30 times compared to the control. Besides, calcium content and content of hydrocarbons changed significantly. Although the soil samples obtained after three months (except for sodium) had a significant decrease in the content of alkaline cations, their levels in the upper soil layer exceeded significantly the control. Conclusions After surface fires, the soil pH is higher as a result of the increase in the content of alkali metals (especially potassium) coming into the soil from the ash formed when litter mortmass and organic substances in the upper humus become combusted. At it happens once, these elements are gradually washed away. The pH is approaching its natural level after some time, especially at the depth. There is no significant inflow of elements to the depth of more than 10 cm. 9 Tables, 22 Refs.